Shuni virus in Israel: Neurological disease and fatalities in cattle. Issue 3 (29th March 2019) - Golender, Natalia; Bumbarov, Velizar; Assis, Itay; Beer, Martin; Khinich, Yevgeny; Koren, Ori; Edery, Nir; Eldar, Avi; Wernike, Kerstin
Summary: The insect‐transmitted Shuni virus (SHUV) belongs to the Simbu serogroup of orthobunyaviruses and it is known to induce abortions, stillbirths and severe congenital malformations in ruminants and may cause neurological signs in infected horses. Here, SHUV was detected in brain samples of two Israeli cattle, which suffered from severe neurological signs that led to the deaths of the animals. During histopathological examination of the first case, a 5‐month‐old calf, small perivascular cuffs, composed mainly of neutrophils with few lymphocytes were observed in the brain stem and cerebrum. Similar infiltrates were also found to a lesser extent in the cerebellar meninges leading to the diagnosis of acute‐subacute meningoencephalitis. The histological examination of the brainstem from the second case, a 16‐month‐old heifer, revealed perivascular infiltration composed of equal numbers of macrophages and neutrophils associated with cerebral and meningeal haemorrhages. In this case encephalitis was diagnosed. Viral RNA was extracted from brain samples of both cattle that suffered from severe neurological signs and was subsequently tested by a polymerase chain reaction PCR assay specific for Simbu serogroup viruses and found positive. The presence of SHUV was subsequently confirmed by the isolation of the virus from one sample and sequence analysis of both brain samples. The comparison of the complete sequences of the coding regions of all three genome segments from both cases revealed a close relationship to Shuni viruses detected in tissue samples of aborted or malformed calves or lambs born during the last years in Israel.